Simultaneous determination of 20 disperse dyes in foodstuffs by ultra high performance liquid chromatography–tandem mass spectrometry. (1st December 2019) - Liu, Weiguo; Liu, Jun; Zhang, Yu; Chen, Yinguang; Yang, Xiaodong; Duan, Luchun; Dharmarajan, Rajarathnam; Wang, Xiyuan; Li, Lan
Highlights: An efficient, fast and sensitive method is developed utilizing UHPLC-MS/MS. The determination method of 20 disperse dyes in complex food matrices is optimized. The monitoring analysis for its robust, time efficient and low cost is valuable. This method is an accurate method with successful application in real samples. The method is suitable to ensure the food safety in screening illegal disperse dyes. Abstract: A reasonable, high sensitive and accurate analytical method for the determination of 20 allergenic disperse dyes in foodstuffs was developed and validated. The obtained results showed that an ultra high liquid performance chromatography system – equipped with tandem quadrupole mass spectrometry (UHPLC–MS/MS) proved to be ideal for the selected method enabling multidimensional processing of the samples. Under optimized conditions, validation results showed excellent linearity (5–1000 µg/L, r 2  ≥ 0.997), limits of detection (LODs, 1.1–10.8 μg/kg), recoveries (60.2–110.3%) and precision (RSDs ≤ 12.6%) for the twenty disperse dyes under investigation. The developed method was successfully applied to the analysis of 20 disperse dyes in real foodstuffs demonstrating the validity and applicability of the current method for continuing monitoring of the selected dyes. The proposed UHPLC-MS/MS is thus proved to be a convenient, effective, sensitive and timesaving method for the isolation and determination of allergenic disperse dyes in edible packaging and other foodstuffs.